Nanometer coating current collector and preparation method thereof
By electrostatically spraying adhesive, conductive agent and divalent alkali powder on the surface of the aluminum foil, the nanocoated current collector is formed, which solves the problems of complex production and high energy consumption in the prior art, and achieves efficient wetting and dense coating formation suitable for large-scale production.
Patent Information
- Application Number
- CN202311231167.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The existing nanoconductive coating current collector uses alkali as an additive during the preparation process, resulting in complex production processes and large energy consumption, which are not suitable for large-scale production. At the same time, the aqueous slurry is difficult to wet the surface of the rolled aluminum foil.
The surface of the aluminum foil is sprayed with electrostatic spraying, conductive agent powder and divalent alkali powder, and the nanocoated current collector is formed by drying, which simplifies the mixing process and is suitable for large-scale operations.
The problem of divalent alkali insoluble in water is solved, the production process is simplified, energy consumption is reduced, and the surface of the aluminum foil is effectively wetted, forming a dense conductive and adhesive coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano conductive coating current collector preparation, in particular to a nano coating current collector and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics, electric vehicles and other fields, and the market has also put forward higher requirements for the energy density, cycle life, and safety of lithium-ion batteries. The current collector conductive primer technology can effectively reduce the contact resistance between the electrode material and the current collector, increase the adhesion between the electrode material and the current collector, reduce the internal resistance of the battery, and extend the battery life.
[0003] The nano-conductive coating current collector generally adopts an aqueous slurry containing a conductive agent and an aqueous binder during the preparation process, and uses alkali as an additive to increase the peel strength. At the same time, it can neutralize the acidity of the binder (such as PAA) and protect the stirring equipment and coating production equipment.
[0004] However, alkali (such as calcium hydroxide) is not soluble in water, has a complex production process, and consumes a lot of energy, which is not conducive to mass production. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a nano-coated current collector and a preparation method thereof. The mixed binder powder, conductive agent powder and divalent base powder are sprayed onto the surface of the aluminum foil. The mixing method is simple and convenient and suitable for large-scale operations. On the one hand, it solves the problem that divalent bases such as calcium hydroxide are insoluble in water. On the other hand, it can also solve the problem that the aqueous slurry wets the rolled aluminum foil (containing oil on the surface).
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] In a first aspect, a method for preparing a nano-coating current collector comprises:
[0008] Providing an aluminum foil;
[0009] Using electrostatic spraying, spraying materials on the surface of the aluminum foil to obtain aluminum foil coated with a material coating; the materials include: binder powder, conductive agent powder and divalent alkali powder;
[0010] The aluminum foil coated with the material coating is dried under preset temperature conditions to obtain a nano-coating current collector layer.
[0011] Preferably, the material is prepared by the following method:
[0012] Mixing the binder powder, the conductive agent powder and the divalent alkali powder uniformly to obtain a mixed material;
[0013] The solvent is gradually added to the mixture and stirred for 2 to 6 hours to form a uniform material.
[0014] Preferably, the weight percentages of the binder powder, the conductive agent powder and the divalent base powder are respectively:
[0015] Binder powder 1-15%, conductive agent powder 0.1-5%, divalent alkali powder 0.1-10%.
[0016] Preferably, the binder powder, the conductive agent powder and the divalent base powder are mixed uniformly to obtain a mixed material, comprising:
[0017] pouring the binder powder into a mixing bowl or container;
[0018] gradually adding the conductive agent powder and the divalent base powder at a rate of 50 g per minute over 5 to 10 minutes to obtain a mixed material;
[0019] Observe the particle distribution of the mixed material using a microscope with 20 times magnification. If agglomeration is observed, screen it using a 300-mesh sieve to obtain a screened material with a mesh size of less than 300;
[0020] The screened materials are uniformly mixed together at room temperature using a stirring rod or a stirrer to obtain a mixed material.
[0021] Preferably, the stirring speed is 450-550 rpm, and the stirring time is 12-18 minutes.
[0022] Preferably, the diameter of the binder powder is 0.5 to 1 μm, the diameter of the conductive agent powder is 0.5 to 3 μm, and the diameter of the divalent base powder is 0.5 to 1 μm.
[0023] Preferably, the binder powder comprises:
[0024] 5-10% by weight of polyvinylidene fluoride;
[0025] 10% to 20% by weight of polyester;
[0026] The weight percentage of the carboxymethyl cellulose and styrene-butadiene rubber mixture is 5-10%.
[0027] Preferably, the conductive agent powder comprises:
[0028] 1% to 5% by weight of graphite;
[0029] 1% to 5% by weight of carbon black;
[0030] The weight percentage of polypyrrole is 1% to 5%.
[0031] Preferably, the aluminum foil coated with the material coating is dried under a preset temperature condition to obtain a nano-coating current collector layer, comprising:
[0032] The coated aluminum foil is left at room temperature for a period of time to allow part of the solvent to evaporate naturally;
[0033] After natural drying, the aluminum foil is placed in a drying furnace, and under certain vacuum conditions, the remaining solvent is evaporated by increasing the temperature, and the binder is solidified to obtain a nano-coating current collector layer.
[0034] In a second aspect, a nano-coating current collector is provided, wherein the nano-coating current collector is obtained by the method described.
[0035] The above solution of the present invention includes at least the following beneficial effects:
[0036] The above scheme of the present invention adopts the method of electrostatic spraying to spray the material on the surface of the aluminum foil. Electrostatic spraying can help the material to evenly cover the surface of the aluminum foil to form a coating. Drying can remove the solvent and moisture in the coating and solidify the coating. Drying under preset temperature conditions can control the drying speed of the coating, so that it produces a certain shrinkage stress, which is conducive to forming a dense coating. The coating has conductivity and adhesion and can be used as a current collector layer. The mixing method is simple and convenient and suitable for large-scale operations. On the one hand, it solves the problem that divalent alkalis such as calcium hydroxide are insoluble in water, and on the other hand, it can also solve the problem of aqueous slurry wetting the rolled aluminum foil (with oil on the surface). DETAILED DESCRIPTION
[0037] An embodiment of the present invention provides a method for preparing a nano-coating current collector, the method comprising:
[0038] (1) providing an aluminum foil;
[0039] (2) spraying a material on the surface of the aluminum foil by electrostatic spraying to obtain an aluminum foil coated with a material coating; the material includes: a binder powder, a conductive agent powder and a divalent alkali powder;
[0040] (3) Drying the aluminum foil coated with the material coating under preset temperature conditions to obtain a nano-coated current collector layer.
[0041] According to a specific implementation, the material is prepared by: uniformly mixing binder powder, conductive agent powder and divalent base powder to obtain a mixed material; gradually adding a solvent to the mixed material and stirring for 2 to 6 hours to form a uniform material.
[0042] According to a specific implementation, the weight percentages of the binder powder, the conductive agent powder and the divalent alkali powder are: 1-15% of the binder powder, 0.1-5% of the conductive agent powder, and 0.1-10% of the divalent alkali powder.
[0043] According to a specific implementation, the binder powder, the conductive agent powder and the divalent base powder are mixed uniformly to obtain a mixed material, including: pouring the binder powder into a mixing bowl or container; gradually adding the conductive agent powder and the divalent base powder at a rate of 50 grams per minute within 5 to 10 minutes to obtain a mixed material; using a microscope with 20 times magnification to observe the particle distribution of the mixed material, if agglomeration is observed, using a 300-mesh sieve to screen to obtain a screened material of less than 300 mesh; using a stirring rod or a stirrer to uniformly mix the screened materials together at room temperature to obtain a mixed material, wherein the stirring speed is 450 to 550 rpm and the stirring time is 12 to 18 minutes.
[0044] According to a specific embodiment, the diameter of the binder powder is 0.5 to 1 μm, the diameter of the conductive agent powder is 0.5 to 3 μm, and the diameter of the divalent base powder is 0.5 to 1 μm.
[0045] According to a specific implementation, the binder powder includes: 5-10% by weight of polyvinylidene fluoride; 10-20% by weight of polyate; and 5-10% by weight of a mixture of carboxymethyl cellulose and styrene-butadiene rubber.
[0046] According to a specific embodiment, the conductive agent powder includes: 1% to 5% by weight of graphite; 1% to 5% by weight of carbon black; and 1% to 5% by weight of polypyrrole.
[0047] According to a specific implementation, the aluminum foil coated with the material coating is dried under preset temperature conditions to obtain a nano-coating current collector layer, including: leaving the coated aluminum foil at room temperature for a period of time to allow part of the solvent to evaporate naturally; after natural drying, the aluminum foil is placed in a drying furnace, and under certain vacuum conditions, the remaining solvent is evaporated by heating, and the binder is solidified to obtain a nano-coating current collector layer.
[0048] The technical solution of the present invention is described below by means of specific embodiments. It should be noted that these examples are only used to help those skilled in the art understand and should not be regarded as limiting the scope of protection of the present invention.
[0049] Example 1
[0050] Example 1 provides a nano-coating current collector, which is prepared by the following method:
[0051] S1: provide an aluminum foil;
[0052] S2: spraying a material on the surface of the aluminum foil by electrostatic spraying to obtain an aluminum foil coated with a material coating; the material includes the following materials in weight percentage: 1% of binder powder, 0.1% of conductive agent powder, and 0.1% of divalent alkali powder;
[0053] The material is prepared by the following method: pouring the binder powder into a mixing bowl or container; gradually adding the conductive agent powder and the divalent base powder at a rate of 50 grams per minute within 5 minutes to obtain a mixed material; using a microscope with 20 times magnification to observe the particle distribution of the mixed material, if agglomeration is observed, using a 300-mesh sieve to screen to obtain a screened material of less than 300 mesh; using a stirring rod or a stirrer to uniformly mix the screened materials at room temperature to obtain a mixed material, wherein the stirring speed is 450 rpm and the stirring time is 12 minutes; adding a solvent that is soluble in the mixed material to the mixed material at a rate of 500 ml per hour; mixing the solvent and the mixed material at a stirring speed of 300 rpm for 2 hours to obtain the material;
[0054] The diameter of the binder powder is 0.5 μm, the diameter of the conductive agent powder is 0.5 μm, and the diameter of the divalent base powder is 0.5 μm;
[0055] The binder powder includes: 5% by weight of polyvinylidene fluoride; 10% by weight of polyester; 5% by weight of a mixture of carboxymethyl cellulose and styrene-butadiene rubber; the conductive agent powder includes: 1% by weight of graphite; 1% by weight of carbon black; 1% by weight of polypyrrole;
[0056] S3: leaving the coated aluminum foil at room temperature for a period of time to allow part of the solvent to evaporate naturally; after natural drying, the aluminum foil is placed in a drying furnace, and under certain vacuum conditions, the remaining solvent is evaporated by increasing the temperature, and the binder is solidified to obtain a nano-coating current collector layer.
[0057] Example 2
[0058] Embodiment 2 provides a nano-coating current collector. The difference between Embodiment 2 and Embodiment 1 is that the material includes the following materials in weight percentage: 7% binder powder, 0.3% conductive powder, and 5% divalent base powder. The diameter of the binder powder is 0.7 μm, the diameter of the conductive powder is 1.7 μm, and the diameter of the divalent base powder is 0.8 μm; the binder powder includes: 7.25% polyvinylidene fluoride by weight; 15% polyate by weight; 7.5% carboxymethyl cellulose and styrene-butadiene rubber mixture by weight; the conductive powder includes: 3% graphite by weight; 3% carbon black by weight; and 3% polypyrrole by weight.
[0059] Example 3
[0060] Example 3 provides a nano-coating current collector. The difference between Example 3 and Example 1 is that the material includes the following materials in weight percentage: 15% binder powder, 5% conductive powder, and 10% divalent base powder. The diameter of the binder powder is 1 μm, the diameter of the conductive powder is 3 μm, and the diameter of the divalent base powder is 1 μm; the binder powder includes: 10% polyvinylidene fluoride by weight; 20% polyate by weight; 10% carboxymethyl cellulose and styrene-butadiene rubber mixture by weight; the conductive powder includes: 5% graphite by weight; 5% carbon black by weight; and 5% polypyrrole by weight.
[0061] Comparative Example 1
[0062] A method for preparing a highly conductive nano-coated current collector comprises the following steps:
[0063] 1 kg of isophorone diisocyanate and 0.5 kg of graphene oxide were uniformly mixed in a solvent of butyl acetate, filtered after the reaction was completed, and then reacted with 0.5 kg of hydroxyethyl acrylate to obtain a modified intermediate; then 1 kg of the modified intermediate was dissolved in 10 kg of acrylic acid and slowly added dropwise to a reactor for emulsion polymerization at a reaction temperature of 70° C. for a reaction time of 8 hours, and a persulfate compound was added to obtain a graphene oxide grafted binder emulsion, and the solid content was adjusted to 25%; 10 kg of conductive carbon black, 20 kg of the obtained graphene oxide grafted binder emulsion, and 157.5 kg of water were mixed and dispersed for 4 hours to obtain a high-conductive nano-coating slurry with a solid content of 8%; the high-conductive nano-coating slurry was coated on both sides of a 13 μm aluminum current collector with a coating machine at a thickness of 1 μm, and a high-conductive nano-coating current collector was obtained after drying.
[0064] The nano-coating current collector prepared in the above embodiment and the nano-coating current collector prepared in the above comparative example are compared as follows:
[0065] Table 1 Results corresponding to different embodiments and comparative examples
[0066]
[0067]
[0068] From the data given in Table 1, it can be seen that the aluminum current collectors prepared in Examples 1 to 3 have the following differences from those in Comparative Example 1:
[0069] 1. Selection of binder. The binders used in Examples 1 to 3, such as polyvinylidene fluoride, polyate and carboxymethyl cellulose and styrene-butadiene rubber mixture, are all high-performance binders widely recognized in the industry. They not only provide good adhesion but also have excellent stability, which means that the performance of the product will not easily deteriorate after long-term use or in harsh environments.
[0070] 2. Selection of conductive agent. Graphite, carbon black and polypyrrole are all highly conductive materials, especially graphite, which is widely used in batteries and supercapacitors because it provides high conductivity and good stability, which means that the product in the embodiment has great potential in conductivity.
[0071] 3. Control of particle size: By clearly specifying the diameter of various powders, the consistency and performance of the product can be ensured. Particle size is critical to many applications because it can affect the dispersion, adhesion and other important properties of the material.
[0072] 3. Environmental friendliness: The raw materials used in Examples 1 to 3 are relatively simple and do not involve harmful chemicals. This not only reduces production costs, but also reduces potential impacts on the environment. In contrast, chemicals such as isophorone diisocyanate used in Comparative Example 1 may cause harm to the environment.
[0073] 4. Preparation process. The preparation process of Examples 1 to 3 is simple and does not involve complex chemical reactions, which means that the waste and emissions generated during the production process will be greatly reduced, thereby reducing the impact on the environment.
[0074] 5. Safety: Since no harmful chemicals are used in Examples 1 to 3, the health risks of operators during the production process are also reduced, which is beneficial to the working environment of the factory and the health of the employees.
[0075] In summary, from the technical solution point of view, Example 1, Example 2 and Example 3 not only have advantages in performance, but also have obvious advantages in environmental friendliness.
[0076] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nano-coating current collector, characterized in that: The method comprises: Providing an aluminum foil; Using electrostatic spraying, spraying materials on the surface of the aluminum foil to obtain aluminum foil coated with a material coating; the materials include: binder powder, conductive agent powder and divalent alkali powder; The aluminum foil coated with the material coating is dried under preset temperature conditions to obtain a nano-coated current collector.
2. The method for preparing a nano-coating current collector according to claim 1, characterized in that: The material is prepared by the following method: The binder powder, the conductive agent powder and the divalent alkali powder are mixed uniformly to obtain a mixed material.
3. The method for preparing a nano-coating current collector according to claim 2, characterized in that: The weight percentages of the binder powder, the conductive agent powder and the divalent alkali powder are respectively: Binder powder 1-15%, conductive agent powder 0.1-5%, divalent alkali powder 0.1-10%.
4. The method for preparing a nano-coating current collector according to claim 2, characterized in that: The binder powder, the conductive agent powder and the divalent alkali powder are mixed uniformly to obtain a mixed material, including: pouring the binder powder into a mixing bowl or container; gradually adding the conductive agent powder and the divalent base powder at a rate of 50 g per minute over 5 to 10 minutes to obtain a mixed material; Observe the particle distribution of the mixed material using a microscope with 20 times magnification. If agglomeration is observed, screen it using a 300-mesh sieve to obtain screened material with a particle size of less than 48 microns; The screened materials are uniformly mixed together at room temperature using a stirring rod or a stirrer to obtain a mixed material.
5. The method for preparing a nano-coating current collector according to claim 4, characterized in that: The stirring speed is 450-550 rpm, and the stirring time is 12-18 minutes.
6. The method for preparing a nano-coating current collector according to claim 5, characterized in that: The diameter of the binder powder is 0.5 to 1 μm, the diameter of the conductive agent powder is 0.5 to 3 μm, and the diameter of the divalent base powder is 0.5 to 1 μm.
7. The method for preparing a nano-coating current collector according to any one of claims 4 to 6, characterized in that: The binder powder comprises: 5-10% by weight of polyvinylidene fluoride; 10% to 20% by weight of polyester; The weight percentage of the carboxymethyl cellulose and styrene-butadiene rubber mixture is 5-10%.
8. The method for preparing a nano-coating current collector according to claim 1, characterized in that: The conductive agent powder comprises: 1% to 5% by weight of graphite; 1% to 5% by weight of carbon black; The weight percentage of polypyrrole is 1% to 5%.
9. The method for preparing a nano-coating current collector according to claim 8, characterized in that: The aluminum foil coated with the material coating is dried under a preset temperature condition to obtain a nano-coating current collector layer, comprising: The coated aluminum foil is left at room temperature for a period of time to allow part of the solvent to evaporate naturally; After natural drying, the aluminum foil is placed in a drying furnace, and under certain vacuum conditions, the remaining solvent is evaporated by increasing the temperature, and the binder is solidified to obtain a nano-coating current collector layer.
10. A nano-coated current collector, characterized in that: The nano-coating current collector is obtained by the method according to any one of claims 1 to 9.